COMPLEMENTARY THERAPY IN IMPROVING THE SLEEP QUALITY OF HEMODIALYSIS PATIENTS: A SCOPING REVIEW - Mesya, M; Permana, Iman (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Complementary therapy can be used as an alternative in treating sleep disturbance among hemodialysis patients. This study intends to pinpoint certain complementary treatment approaches that can enhance hemodialysis patients' sleep quality using Scooping Review. The databases Scopus, Proquest, PubMed, and ScientDirect are the ones that are monitored. The search terms to employ are "Complementary Therapies" OR "Therapy, Complementary" OR "Complementary Medicine" OR "Therapies, Alternative" AND "Sleep Quality" OR "Sleep Qualities" AND "Renal Dialysis" OR "Hemodialysis," with the quality of each keyword being assessed and the results being summarized in the final report. The initial search of 6863 articles were found by filtering according to the inclusion criteria, which included 2012–2022, full text, journal article type, quantitative, qualitative, and mixed methods, and 6842 after duplication check. Screening of titles and abstracts, as well as design, non-English, and deleting articles that did not match left 257 articles. Finally, 11 articles were left for eligibility assessments based on the inclusion and exclusion. There are four types of complementary therapy that can be used to enhance sleep quality, including dietary supplements; mind-body modalities; acupuncture, acupressure; and massage. For individuals receiving hemodialysis, this therapy may be a good non-pharmacological alternative to treat sleep issues. To validate these results and advance knowledge of complementary therapies for controlling sleep quality in hemodialysis patients, additional study is required.